Peningkatan Mutu Pendidikan Anak Usia Dini melalui Peningkatan Profesionalitas Guru - Yusutria Yusutria (Pusat Penerbitan Universitas (P2U) Unisba, 2019)
The purpose of this study was to determine the efforts to improve the professionalism of PAUD teachers in improving the quality of Harapan Bangsa City PAUD education. Qualitative descriptive research method, while data collection techniques are based on observation, interviews, documentation. The data analysis techniques are based on data reduction, data presentation, and conclusions. PAUD institutional constraints include educational qualifications, experience, infrastructure, managers, welfare. Efforts to improve the professionalism of PAUD teachers by providing scholarships, workshops, seminars, adequate facilities, and infrastructure, as well as maintaining smooth communication with both foundations, teachers, and parents.Keywords: Professionalism, PAUD Teachers, Quality of Education Abstrak Tujuan dari penelitian ini adalah untuk mengetahui upaya meningkatkan profesionalitas guru PAUD dalam meningkatan mutu pendidikan PAUD Harapan Bangsa Kota Padang. Metode penelitian deskriptif kualitatif, sementara teknik pengumpulan data berdasarkan dengan observasi, wawancara, dokumentasi. Adapun teknik analisis data berdasarkan pada reduksi data, penyajian data dan kesimpulan. Kendala lembaga PAUD di antaranya kualifikasi pendidikan, pengalaman, sarana prasarana, pengelola, kesejahteraan. Upaya meningkatkan profesionalisme guru PAUD dengan memberikan beasiswa, workshop, seminar, fasilitas sarana prasarana yang memadai, serta tetap menjaga lancarnya komunikasi baik dengan pihak yayasan, guru, dan orang tua. Kata Kunci: Profesionalitas, Guru PAUD, Mutu Pendidikan.